Development of the Dutch Structure for Integrated Children's Palliative Care - Stephanie Vallianatos; Carolien S. M. Huizinga; Meggi A. Schuiling-Otten; Antoinette Y. N. Schouten-van Meeteren; Leontien C. M. Kremer; A. A. Eduard Verhagen (MDPI AG, 2021)
Children's palliative care (CPC) is gaining attention worldwide, facilitated by the exchange of knowledge during regular specialised congresses. This article describes the developments in the Netherlands over the past 15 years. The Foundation for Children's Palliative Expertise (PAL) was established as a nationwide initiative committed to improving palliative care for children countrywide. This led to the development of the first hospital-based CPC team in 2012, which expanded to a total of seven teams adjacent to children's university hospitals. Regional networks for CPC were developed in parallel to these teams from 2014 onwards. The networks are a collaboration of professionals from different disciplines and organisations, from hospital to homecare, and have covered the aspects of CPC nationally from 2019 onwards. They are connected through the Dutch Knowledge Centre for CPC. This centre was established in 2018 by the PAL Foundation in collaboration with the Dutch Association for Pediatrics. In 2013, the first evidence-based guideline, 'palliative care for children', provided access to knowledge for parents and healthcare providers, and in 2017, a format for an individual palliative care plan was established. Within the Knowledge Centre for CPC, a physician's support centre for dilemma's regarding the end of life of children was set up. The efforts to have children's palliative care embedded in the regular Dutch health care insurance are ongoing.